Storytelling and Policy Transfer - Titilayo Soremi (International Review of Public Policy)
This article argues that policy narratives underpin the mechanisms driving policy transfers. It applies the Narrative Policy Framework (NPF) to examine the policy narratives of the transfer agent and recipient, involved in the introduction of disaster risk reduction policy to West Africa. The article analyses the narrative setting, character, plot and moral depicted by the actors in their policy narratives and explains how these narrative elements informed the observation of the transfer mechanism of obligation.